PLUNC 3D Radiation Treatment Planning System (TPS): An Educational Platform for Medical Physics Students - Mollah, Abdus Sattrar (Bangladesh Journal of Nuclear Medicine, 2018)
Technological innovations with modern planning and treatment techniques have transformed the way of radiation treatment for cancer patients. A tremendous evolution in radiation treatment process occurred in recent years. This allowed the delivery of the desired radiation dose distribution to target tissue, while delivering an acceptable radiation dose to the surrounding normal tissues with greater dose gradients and tighter margins. Evolution of the computers and computerized systems enabled the possibility to improve the basic two-dimensional (2D) radiotherapy treatment planning to a more accurate and more visualised three-dimensional (3D) treatment planning systems. Today there is now several commercialized planning system competitors used for external beam radiation therapy. PLUNC was one of the first operating 3D radiation treatment planning (RTP) systems’. This RTP system has been developed in the Department of Radiation Oncology at the University of North Carolina (UNC) since 1985 for research and educational purposes. PLUNC is freely distributed to the field of radiation oncology for research and educational use under special license agreement. In this study, PLUNC 3D treatment planning system has been installed and implemented for research and educational purpose in the field of medical physics. A 3D treatment plan has been created and analyzed in a typical patient CT image for educational demonstration purpose. Based on this analysis, it is concluded that the PLUNC 3D TPS could be successfully used for research and education purposes in M Sc/PhD thesis works of students from medical physics discipline. Bangladesh J. Nuclear Med. 21(1): 35-42, January 2018